Tra il naturalismo di ‘costì’ e il verismo ‘di qui’: Capuana recensore di Rod, Rod critico di Capuana - Muoio, Ilaria (Incontri. Rivista europea di studi italiani, 2018)
Between the Naturalism ‘from there’ and the Verismo ‘from here’: Capuana as a reviewer of Rod’s work and Rod as a critic of Capuana’sThe first meeting - purely epistolary - between Édouard Rod and Luigi Capuana dates back to June 1882. Giovanni Verga, who had recently met the Swiss-Parisian intellectual in the French capital, becomes their intermediary as he suggests Capuana to send his works to Rod and, at the same time, suggests Rod to send his novel Côte a Côte (1882) to Capuana, a successful militant critic. Thus, an intense correspondence begins between the two writers, whose stages are reconstructed by Jean-Jacques Marchand in Edouard Rod et les écrivains italiens (1980). Their exchange of letters alternately continues until 1909, accompanied by a real exchange of courtesies: from France, Rod regularly reviewes the short stories and the critical studies of the Sicilian writer and, from Italy, Capuana makes Rod the privileged dedicatee of his last production and evaluates his works with critical rigor on the most important newspaper’s columns of the time. A cross-examination of these writings - in most cases relegated to a first publication on specialised magazines - and the contents expressed in their missives reveals a significant reflection on the differences between the French Naturalism and the Italian Verismo, as well as a mutual effort to redefine the concept of influence. The stages of the epistolary relationship between the two writers are reconstructed here, linked to an initial analysis of the critical debate on Capuana’s work in France and Rod’s work in Italy.